1994
DOI: 10.1136/oem.51.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural objective tests in the assessment of hand-arm vibration syndrome.

Abstract: Assessment (staging) of workers exposed to vibration, based solely on a subjective history, has been shown to be unsatisfactory. The internationally agreed use of a sensorineural component in the Stockholm classification requires the use of sensory objective tests. Four hundred and twenty two subjects were assessed by a subjective history supplemented by multiple objective tests. These tests covered the vascular, sensorineural, musculoskeletal and dexterity aspects of hand-arm vibration syndrome. Tests to help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Few studies have addressed the question of vibration exposure and vibrotactile perception. Vibrotactile perception thresholds among vibration exposed workers have been measured in relation to the staging of HAVS [Hayward and Griffin, 1986;McGeoch et al, 1994] and in comparison to other methods of assessing vibration-neuropathy [Sakakibara et al, 1996]. Other investigators have focused on the distribution of vibrotactile impairment in the hands of vibration-exposed patients .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have addressed the question of vibration exposure and vibrotactile perception. Vibrotactile perception thresholds among vibration exposed workers have been measured in relation to the staging of HAVS [Hayward and Griffin, 1986;McGeoch et al, 1994] and in comparison to other methods of assessing vibration-neuropathy [Sakakibara et al, 1996]. Other investigators have focused on the distribution of vibrotactile impairment in the hands of vibration-exposed patients .…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative tests such vibrotactile and thermal perception thresholds, hand-grip strength and manipulative dexterity have been widely used in HAVS assessment. Lawson and McGeoch [1,6,20] have derived and applied a system within which the use of such tests is clearly defined and integral to assessing Stockholm workshop staging. This was closely related to the 'standardization' of quantitative tests, such as vibrotactile and thermal perception, in the UK [12,21].…”
Section: Discussionmentioning
confidence: 99%
“…A battery of established quantitative tests have been applied in the assessment of vibration exposed individuals including vibrotactile and thermal perception thresholds, Purdue pegboard and grip strength [6,7]. The vibrotactile and thermal perception tests assess specific receptor and sensory nerve damage in the hand/fingers.…”
Section: Introductionmentioning
confidence: 99%
“…McGeoch et al (1994) reported much more severe symptoms (25% at stage SN2 and 9% at stage SN3); the population however, was much older and had had, on average, 25 years of exposure to vibration.…”
Section: Discussionmentioning
confidence: 96%